2015
DOI: 10.3748/wjg.v21.i8.2522
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: Is combination of tetracycline and amoxicillin suitable forHelicobacter pyloriinfection?

Abstract: The effectiveness of regimens employing amoxicillin and tetracycline for H. pylori eradication may be not inferior to other regimens, but further study should be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 67 publications
1
19
0
2
Order By: Relevance
“…Six studies exclusively evaluated second-line treatment for patients with at least one prior course of treatment failure [ 27 32 ]; 12 studies focused on treatment naive patients [ 25 , 26 , 33 42 ]; the remaining systematic reviews included RCTs for both first-line and second-line treatment. 13 studies evaluated treatments in patients with comorbid gastric diseases including peptic ulcer disease, duodenal ulcer, functional dyspepsia, chronic gastritis or other non-ulcer diseases [ 24 , 27 , 37 40 , 43 49 ] (the remaining studies did not provide such data). In addition to the eradication rate, 15 systematic reviews also compared adverse events rates [ 25 , 28 38 , 41 , 47 , 50 ] and six compared the discontinuity rate (compliance rate) [ 25 , 29 31 , 37 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies exclusively evaluated second-line treatment for patients with at least one prior course of treatment failure [ 27 32 ]; 12 studies focused on treatment naive patients [ 25 , 26 , 33 42 ]; the remaining systematic reviews included RCTs for both first-line and second-line treatment. 13 studies evaluated treatments in patients with comorbid gastric diseases including peptic ulcer disease, duodenal ulcer, functional dyspepsia, chronic gastritis or other non-ulcer diseases [ 24 , 27 , 37 40 , 43 49 ] (the remaining studies did not provide such data). In addition to the eradication rate, 15 systematic reviews also compared adverse events rates [ 25 , 28 38 , 41 , 47 , 50 ] and six compared the discontinuity rate (compliance rate) [ 25 , 29 31 , 37 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the Fourth Chinese National Consensus , we recommended five therapy regimens, including classical bismuth‐containing quadruple therapy . Since then, we further extended two regimens of bismuth‐containing quadruple therapy (PPI + bismuth + amoxicillin + metronidazole, PPI + bismuth + amoxicillin + tetracycline) . The composition of these regimens, drug dosages, and usage is shown in Table .…”
Section: Treatmentmentioning
confidence: 99%
“…Each of them has its own antibacterial spectrum and advantages. Amoxicillin trihydrate, a common treatment for peptic or gastric ulcers caused by H. pylori infection, 186 loaded in κ-carrageenan hydrogels containing CaCO 3 and NaHCO 3 or CS/polygamma-glutamic acid nanoparticle pH-sensitive hydrogels was well protected from the gastric juice, thus facilitating drug effects specifically at the site of infection. 187,188 The similar results of in vivo studies by Moogooee et al 189 showed that the amoxicillin-loaded hydrogels enhance drug concentration at the topical site than powder amoxicillin, meaning that therapeutic concentration can be achieved at a much lower dose which may reduce the adverse effects of amoxicillin in high doses.…”
Section: Other Antibioticsmentioning
confidence: 99%